Therapeutic Application of Micellar Solubilized Xanthohumol in a Western-Type Diet-Induced Mouse Model of Obesity, Diabetes and Non-Alcoholic Fatty Liver Disease - Mahli, Abdo; Seitz, Tatjana; Freese, Kim; Frank, Jan; Weiskirchen, Ralf; Abdel-Tawab, Mona; Behnam, Dariush; Hellerbrand, Claus (Cells, 2019)
Xanthohumol (XN), a prenylated chalcone from hops, has been reported to exhibit a variety of health-beneficial effects. However, poor bioavailability may limit its application in the prevention and therapy of diseases. The objective of this study was to determine whether a micellar solubilization of xanthohumol could enhance the bioavailability and biological efficacy of xanthohumol in a Western-type diet (WTD) induced model of obesity, diabetes and non-alcoholic fatty liver disease (NAFLD). After 3 weeks feeding with WTD, XN was additionally applied per oral gavage as micellar solubilizate (s-XN) or native extract (n-XN) at a daily dose of 2.5 mg/kg body weight for a further 8 weeks. Control mice received vehicle only in addition to the WTD. WTD-induced body weight-gain and glucose intolerance were significantly inhibited by s-XN application. Furthermore, WTD-induced hepatic steatosis, pro-inflammatory gene expression (MCP-1 and CXCL1) and immune cell infiltration as well as activation of hepatic stellate cells (HSC) and expression of collagen alpha I were significantly reduced in the livers of s-XN-treated mice compared to WTD controls. In contrast, application of n-XN had no or only slight effects on the WTD-induced pathological effects. In line with this, plasma XN concentration ranged between 100-330 nmol/L in the s-XN group while XN was not detectable in the serum samples of n-XN-treated mice. In conclusion, micellar solubilization enhanced the bioavailability and beneficial effects of xanthohumol on different components of the metabolic syndrome including all pathological steps of NAFLD. Notably, this was achieved in a dose more than 10-fold lower than effective beneficial doses of native xanthohumol reported in previous in vivo studies.
CRIS-Team WoS Importer:2019-06-18